Implementation of Celebrating Diversity in the Global Diversity Theme Pancasila Student Profile Strengthening Project (P5) in Class VB SD Baiturrohman GMI - Rizkiyah, Maulida Putri; Jamalah, Lailah (IJIE International Journal of Islamic Education, 2023)
Character education is now a focal point in Indonesia's education system, aligning with national development goals to cultivate students who embody faith, piety, noble character, health, knowledge, competence, creativity, independence, and responsibility. To counter the erosion of moral values in adolescents influenced by modernization and globalization, effective character education implementation is crucial. Since the 2013 curriculum is deemed ineffective, the project-based independent curriculum aims to fortify students' characters. SD Baiturrohman GMI Jember is among the schools that have adopted this approach. This qualitative research illustrates the implementation of the Pancasila Student Profile Strengthening Project (P5), emphasizing tolerance in Class V-B SD Baiturrohman GMI. P5, themed "Global Diversity," unfolds in four stages: Variety of Greetings, Celebrations, Virtual Tours, and Collaboration in the Virtual World. Students engage in enjoyable activities like treasure hunting, crafting board games, virtual tourism exploration, and collaborative online ventures. Notably, these activities enhance understanding and practice of tolerance, showcasing the effectiveness of project-based learning facilitated by teachers. However, further efforts are required to ensure all students achieve the P5 goals.